Leadership in Startup Ecosystems and Unicorns: How Successful Startup Leaders Develop a Culture of Innovation and Exponential Growth - Salsabilah Al Fitri; Jessica Fernanda Audrelya; Alfi Manzilatur Rohmah; Mochammad Isa Anshori (Indonesian Economic Review, 2025)
This research investigates the role of leadership in building a culture of innovation and driving rapid growth in startups and unicorn companies. The main objective of this research is to identify the principles of effective leadership as well as the challenges faced in creating a culture of innovation. The methodology used was a case study with a qualitative approach, which included literature analysis and in-depth interviews with leaders from various sectors. The research findings show that successful leaders in startups tend to create an environment that supports experimentation, integrate technology in the work process, and apply collaborative and inclusive leadership principles. In addition, a deep understanding of market dynamics is also an important factor in formulating innovative strategies. Key challenges faced include resistance to change, managing diverse teams, and pressure to adapt to rapid market changes. The article concludes that effective leadership, supported by good communication, adaptability, and collaboration, is a key element in achieving exponential growth and corporate sustainability. Therefore, it is important for organizations to provide training and development for leaders to enhance their skills, thereby creating a more innovative and productive work culture.